2010
DOI: 10.1007/s11255-010-9777-9
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of uropathogens in women with acute uncomplicated cystitis from primary care settings

Abstract: We assessed the antimicrobial resistance patterns of all urine samples submitted for culture from outpatient women aged ≥14 years with diagnosis of uncomplicated cystitis over a 24-month period (2007-2009) in the city of Fortaleza, Brazil. Only bacterial growth of a single uropathogen with ≥10(5) CFU/mL was considered for analysis. The Pearson's chi-square test was used for bivariate correlations. Escherichia coli presented the highest prevalence (64.7%). Coagulase-negative staphylococcus was more common in yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
11
0
4
Order By: Relevance
“…Trimethoprim-sulfamethoxazole is no longer recommended for empirical treatment in many regions of the world. 6,7 Fluoroquinolones remain an effective option; however, resistance rates continue to increase, so this class is often reserved for more complicated infections. 2,8 The prevalence of MDR pathogens being isolated in urine cultures from patients presenting to the ED is increasing, with 19% of all ED urine cultures yielding a causative pathogen resistant to at least 3 common classes of treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Trimethoprim-sulfamethoxazole is no longer recommended for empirical treatment in many regions of the world. 6,7 Fluoroquinolones remain an effective option; however, resistance rates continue to increase, so this class is often reserved for more complicated infections. 2,8 The prevalence of MDR pathogens being isolated in urine cultures from patients presenting to the ED is increasing, with 19% of all ED urine cultures yielding a causative pathogen resistant to at least 3 common classes of treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that analyzed uropathogenic E. coli isolates in the same area revealed a norfloxacin resistance rate of 11.6% in Ponta Grossa ( Bail et al , 2006 ) and 13.8% in Curitiba ( Ito et al , 2008 ). In Fortaleza in the northeast of Brazil, a lower resistance rate of 7.5% was described for norfloxacin ( Araújo et al , 2011 ). In Europe, a multicentric study showed a ciprofloxacin resistance rate from 1.4% to 12.9% ( Schito et al , 2009 ), whereas a higher rate (31%) was registered in the hospitalized population in Ribeirão Preto, Brazil ( Santo et al.…”
Section: Resultsmentioning
confidence: 99%
“…Ressaltamos que a EPS visa a reflexão das ações cotidianas, dessa forma, compreendemos que pôr o trabalho em um processo de análise implica que as ações que contemplam a EPS, devem estar alicerçadas em estratégias dialógicas, visto que, aprendizagem é no trabalho e para o trabalho e é dada como um processo contínuo e dinâmico que necessita da participação ativa dos sujeitos envolvidos 10 .…”
Section: A Educação Permanente Em Saúde No Contexto Do Susunclassified
“…A ideia de desaprender o sujeito que somos encaixados em modelos prévios de trabalho é um convite para experimentar a potência dos ruídos, dos desconfortos e dos estranhamentos. A problematização como uma das características da EPS é a possibilidade de explorar um problema que emperra a produção do cuidado, e aproximar-se do princípio da integralidade pela intencionalidade de colocar em xeque estes ensejos de forma a serem estimulados o diálogo, a interação e a análise crítica 10 . Se somos atores ativos das cenas de formação e trabalho, o que vem a ser a ideia de permanente no SUS?…”
Section: A Educação Permanente Em Saúde No Contexto Do Susunclassified
See 1 more Smart Citation